2012
DOI: 10.1016/j.bbmt.2011.07.023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Complications, Immunologic Effects, and Role of Passage for Outcome in Mesenchymal Stromal Cell Therapy

Abstract: Thirty-one patients treated with mesenchymal stromal cells (MSCs) for acute graft-versus-host disease (aGVHD) or hemorrhagic cystitis between 2002 and 2007 were followed to investigate predictors of outcome, immunologic effects in vivo, and long-term survival. There was no correlation between in vitro suppression by MSCs in mixed lymphocyte cultures and outcome. Soluble IL-2 receptors were measured in blood before and after MSC infusion and declined significantly during the first week after MSC infusion (P = .… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
209
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(221 citation statements)
references
References 22 publications
11
209
0
1
Order By: Relevance
“…However, an improved survival was only noted in patients with complete response, 82 for whom 2-year survival was 53% and long-term survival even worse. 48 The results are more promising when used at an early stage of GVHD. 86 Bernardo et al 96 treated grade-II acute GVHD with MSCs and reported no deaths that were attributable to acute GVHD as compared with 26% in retrospective control patients.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…However, an improved survival was only noted in patients with complete response, 82 for whom 2-year survival was 53% and long-term survival even worse. 48 The results are more promising when used at an early stage of GVHD. 86 Bernardo et al 96 treated grade-II acute GVHD with MSCs and reported no deaths that were attributable to acute GVHD as compared with 26% in retrospective control patients.…”
Section: Discussionmentioning
confidence: 75%
“…At our centre, 31 patients treated with MSCs for acute GVHD or hemorrhagic cystitis were followed for 44 years. 48 The patients who received MSCs from passage 1-2 had better survival (75% at 1 year) than those who received MSCs from passage 3-4 (21%) (Po0.01). Long-term survival was not better than in patients with severe acute GVHD who were not treated with MSCs.…”
Section: Clinical Use Of Bm-derived Mscsmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs show distinct efficacy in graft-versus-host disease (GvHD) patients (18,19) with no, or only minor, side effects. Importantly, no increased risk of tumor development in patients is known, and no ectopic tissue formation has been observed (20,21).…”
mentioning
confidence: 99%
“…As described above, the requirement of repeated administration in industrial MSC therapy probably could arise from their dysfunction induced by bulk production. Von Bahr et al reported that the patients who received MSCs from passage 1-2 have better survival (75% at 1 year) than those who receive MSCs from passage 3-4 (21%) (p < 0.01) [47]. In addition, the immune plasticity of MSCs may vary depending on donors.…”
Section: Problems and Future Directions Of Msc Therapy For Acute Gvhdmentioning
confidence: 99%